Does EMU need stage two? - Stefan Johannes Hack; Wolfgang Maennig (Intereconomics, 1991)
The Delors Committee's three stage plan for attaining European Economic and Monetary Union has met with heavy criticism and has given rise to various counter-proposals. The following article examines the relative merits and shortcomings of the Delors Plan and the alternative concepts presented by the Deutsche Bundesbank and the British Government.
Keywords: 330; European Community